Studies on UV/Visible Absorption and IR Transmission Characteristics of Cu2+ Ion in a Soda-Magnesia-Lime-Silica Glass for Solar Application - Tripathi H.; Kumar A.S.; Kumar V.; Singh A.; Nirala S.K.; Singh S.P. (My University, 2025)
The aim of this investigation is to study the UV/Visible absorption and infra-red transmission characteristics due to Cu+/Cu2+ redox in silica glass. The glass composition 18Na2O-2MgO-8CaO-72SiO2 (mol%) containing different concentrations of CuO were prepared by melting route. The optical absorption spectra of the glasses were recorded on an UV/Visible/NIR spectrophotometer in the wavelength range of 200-1100 nm. The linear absorption coefficient was found to be around 7.60 cm–1 per wt% of CuO in the glass samples. The Cu2+ band was attributed to spin allowed transition from 2Eg →2T2g level in the glass and the applicability of Urbach’s rule was tested for Cu+ ion. It was found that optical band gap for Cu+ was 4.03 eV and its band width was 0.43 eV in the glass. The oscillator strength of the Cu+ ion band (ƒabs) in the glass was reported. The absorption and transmission characteristics of glass containing Cu+ and Cu2+ ions showed a decrease in absorption coefficient of Cu2+ beyond red spectral region. This dictates that glass containing copper ions can be used for IR transmitting purpose and can convert the solar energy into electrical energy for photovoltaic applications. © 2020, © 2020 Indian Ceramic Society.